IbM Peningkatan Psychological Wellbeing pada Guru SMK Muhammadiyah 1 Purwokerto - Wibowo, Ugung Dwi Ario; Suwarti, S (Prosiding University Research Colloquium, 2018)
Society service aims: to help teachers able to interpret the work and life according to the desired psychological conditions, thus requiring increased self-skill to build psychological wellbeing. Society service is used by a number of 28 teachers SMK Muhammadiyah 1 Purwokerto. Training sessions of Psychological Wellbeing on the Teacher are: (1) Know the concept of "self" in yourself; (2) basic concepts and psychological wellbeing; (3) psychological wellbeing development in the workplace; and (4) psychological wellbeing implementation with its work. Training Implementation, using lecture, discussion, worksheet, and relaxation methods. In conclusion, IbM Improvement of psychological wellbeing on teachers SMK Muhammadiyah 1 Purwokerto is appropriately applied as one effort to form the concept of thinking in work that is wellbeing and led to effective working behavior. The inhouse method becomes an appropriate method for understanding and raising psychological wellbeing as an outcome. Follow up. Post-training mentoring in the workplace and simulation in psychological wellbeing.